DNA Capture and Enrichment: A Culture-Independent Approach for Characterizing the Genomic Diversity of Pathogenic Leptospira Species - Nathan E. Stone; Ryelan F. McDonough; Camila Hamond; Karen LeCount; Joseph D. Busch; Katherine L. Dirsmith; Sarai Rivera-Garcia; Fred Soltero; Laura M. Arnold; Zachary Weiner; Renee L. Galloway; Linda K. Schlater; et al. (Microorganisms, 2023)
Because they are difficult to culture, obtaining genomic information from Leptospira spp. is challenging, hindering the overall understanding of leptospirosis. We designed and validated a culture-independent DNA capture and enrichment system for obtaining Leptospira genomic information from complex human and animal samples. It can be utilized with a variety of complex sample types and diverse species as it was designed using the pan-genome of all known pathogenic Leptospira spp. This system significantly increases the proportion of Leptospira DNA contained within DNA extracts obtained from complex samples, oftentimes reaching >95% even when some estimated starting proportions were <1%. Sequencing enriched extracts results in genomic coverage similar to sequenced isolates, thereby enabling enriched complex extracts to be analyzed together with whole genome sequences from isolates, which facilitates robust species identification and high-resolution genotyping. The system is flexible and can be readily updated when new genomic information becomes available. Implementation of this DNA capture and enrichment system will improve efforts to obtain genomic data from unculturable Leptospira-positive human and animal samples. This, in turn, will lead to a better understanding of the overall genomic diversity and gene content of Leptospira spp. that cause leptospirosis, aiding epidemiology and the development of improved diagnostics and vaccines.